Data Quality Analysis on Open Government Data Portals: A Qualitative Study Using ISO/IEC 25012:2008 Standards - Emigawaty, Emigawaty; Syafrianto, Andri (Journal of Information System and Informatics, 2024)
This study evaluates the data quality on Open Government Data (OGD) portals using the ISO/IEC 25012:2008 standard, which categorizes data quality into two main groups: inherent data quality and system-dependent data quality. This standard encompasses dimensions such as accuracy, completeness, consistency, and relevance. Using a qualitative approach, interviews were conducted with data providers and users from the government, industry, and academia. The findings indicate that while some datasets are adequate, there are issues with semantic consistency, completeness, timeliness, and currency of the data. These findings highlight the importance of strict and continuous application of data quality standards in OGD management. Recommendations for improvement include training for data managers and enhancing validation mechanisms before data is published. This study supports government efforts to improve transparency and accountability by providing high-quality data that can be reliably used by various stakeholders.